Biodegradable Polyphosphazene Based Peptide-Polymer Hybrids - Linhardt, Anne (Polymers (Basel), 2016)
A novel series of peptide based hybrid polymers designed to undergo enzymatic degradation is presented, via macrosubstitution of a polyphosphazene backbone with the tetrapeptide Gly-Phe-Leu-Gly. Further co-substitution of the hybrid polymers with hydrophilic polyalkylene oxide Jeffamine M-1000 leads to water soluble and biodegradable hybrid polymers. Detailed degradation studies, via (31)P NMR spectroscopy, dynamic light scattering and field flow fractionation show the polymers degrade via a combination of enzymatic, as well as hydrolytic pathways. The peptide sequence was chosen due to its known property to undergo lysosomal degradation; hence, these degradable, water soluble polymers could be of significant interest for the use as polymer therapeutics. In this context, we investigated conjugation of the immune response modifier imiquimod to the polymers via the tetrapeptide and report the self-assembly behavior of the conjugate, as well as its enzymatically triggered drug release behavior.